2003
DOI: 10.1038/sj.bmt.1704213
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between CsA trough blood concentration and severity of acute graft-versus-host disease after paediatric stem cell transplantation from matched-sibling or unrelated donors

Abstract: Summary:In order to determine optimal CsA trough blood concentrations (TBC) in the early post transplantation period, we analysed relationships between TBC and acute graft-versus-host disease (aGVHD) in paediatric SCT. A total of 94 children consecutively underwent allogeneic stem cell transplantation (SCT) from: matched-sibling (MSD) (n ¼ 36), mismatched-related (MMRD) (n ¼ 3) and unrelated donors (UD) (n ¼ 55). GVHD prophylaxis usually included CsA alone or with methotrexate. Antithymocyte globulin was added… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 31 publications
1
48
0
Order By: Relevance
“…Indeed, we previously reported a strong relationship between CsA TBC during the first 2 weeks post-transplantation, and the severity of aGVHD occurring at engraftment. 8 In the present study, CsA TBC were maintained around 120 ng/mL, even if the intraindividual variability of CsA pharmacokinetics might have led to transient lower or higher concentrations. Our results confirm that the cutoff value 120 ng/mL seems the most relevant to target to trigger off a mild aGvHD in both ALL and AML patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, we previously reported a strong relationship between CsA TBC during the first 2 weeks post-transplantation, and the severity of aGVHD occurring at engraftment. 8 In the present study, CsA TBC were maintained around 120 ng/mL, even if the intraindividual variability of CsA pharmacokinetics might have led to transient lower or higher concentrations. Our results confirm that the cutoff value 120 ng/mL seems the most relevant to target to trigger off a mild aGvHD in both ALL and AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Patients with relapsed ALL were treated according to the risk stratification of BFM relapses protocols. 17 For AML patients in CR1, HSCT was recommended for all patients with monosomy 5 or 7, translocation t(6,9) and mixed lineage leukemia rearrangement, except for translocation t(9,11) with related or unrelated donors, and was performed in other cases with matched sibling donors (MSDs) only, except for patients with translocation t (8,21). 18 All AML relapses were indications to transplant after CR2 was achieved.…”
Section: Patients and Methods Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Previous studies showed that low trough CsA concentration and reduction to less than 80% of the scheduled CsA dose were associated with the onset of grades II-IV acute GVHD. [2][3][4][5] However, these studies did not clarify fully whether low CsA concentrations, after the start of administration, are associated with the onset. Recent study reported that the incidence of grades II-IV acute GVHD was lower in the patients treated with twicedaily infusion of CsA than in those treated with the continuous infusion.…”
Section: Introductionmentioning
confidence: 99%
“…Immunosuppressive therapy between BMT day þ 1 and þ 13 consisted only of cyclosporine infusions, with a twice weekly therapeutic drug monitoring (TDM), to keep a trough blood concentration level between 80 and 100 ng/ml. 10 A grade II GVHD occurred on day þ 13 post BMT and it was decided to add corticoid therapy and increase cyclosporine doses (to reach trough blood concentration levels of 150 ng/ml). GVHD was rapidly controlled.…”
mentioning
confidence: 99%